High hermeticity welding method of glass and metal dissimilar materials

CN122956096APending Publication Date: 2026-10-23JINZHONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611197802.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0008]针对现有技术中的问题,本发明提供了玻璃与金属异种材料高气密性焊接方法,以解决现有技术中存在的界面层结合力弱、应力释放不彻底、玻璃易开裂、高温性能差以及长期可靠性低等问题

Benefits of technology

本发明采用等离子体增强原子层沉积技术制备原子级成分梯度界面层,实现了热膨胀系数的连续线性变化,界面层具有极高的致密度、均匀性和结合力,能够有效缓解残余应力,同时显著提高接头的气密性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956096A_ABST
    Figure CN122956096A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of dissimilar material connection, in particular to a glass and metal dissimilar material high-airtightness welding method, which solves the problems of weak interface bonding force, large residual stress, easy glass cracking, poor high-temperature performance and low long-term reliability existing in the current glass and metal welding. The method sequentially performs surface synergistic pretreatment, plasma-enhanced atomic layer deposition to prepare an atomic-level composition gradient interface layer, femtosecond laser etching combined with nanocrystallization to prepare a double stress self-release structure, laser-induced ultrasonic auxiliary femtosecond-nanosecond double-pulse laser welding, and finally gradient cooling and electric field assisted low-temperature annealing composite post-processing. The helium leakage rate of the welding joint prepared by the present application is still lower than 1x10 ‑12 Pa·m 3 / s after 1000 hours of heat preservation at 150 DEG C, the shear strength retention rate is greater than 85%, the comprehensive performance is excellent, and the use requirements of extreme environments such as aerospace, nuclear industry and deep diving equipment can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of dissimilar material joining technology, specifically a high-airtightness welding method for glass and metal dissimilar materials. Background Technology

[0002] The bonding of glass and metal is a key technology in modern high-end manufacturing, widely used in fields with extremely high requirements for airtightness and reliability, such as aerospace, nuclear industry, deep-sea equipment, semiconductor manufacturing, and medical devices. For example, in the nuclear industry, the windows of nuclear radiation detectors need to be bonded with quartz glass and stainless steel to withstand high temperature, high pressure, and strong radiation environments; in the field of deep-sea equipment, the shells of underwater optical sensors need to be bonded with borosilicate glass and titanium alloys to withstand water pressure at depths of hundreds or even thousands of meters; and in the field of semiconductor manufacturing, the observation windows of vacuum chambers need to be bonded with aluminosilicate glass and Kovar alloys to ensure long-term stability in ultra-high vacuum environments.

[0003] With the continuous development of technology, the performance requirements for glass-metal welded joints are becoming increasingly stringent. These joints not only require extremely high airtightness and strength, but also excellent high-temperature performance, thermal shock resistance, and long-term reliability. However, due to the significant differences in the physical and chemical properties of glass and metal, particularly their vastly different coefficients of thermal expansion, welding them has become a global technical challenge.

[0004] Currently, the main methods for joining dissimilar materials like glass and metal include brazing, diffusion welding, anodic welding, and laser welding. Brazing is the most traditional method, achieving a connection by filling the space between the glass and metal with a low-melting-point filler metal. However, brazed joints have lower airtightness and strength, poor wettability between the filler metal and glass, requiring the use of flux, and flux residue can severely affect the corrosion resistance and long-term reliability of the joint. Diffusion welding achieves a connection through atomic diffusion under high temperature and pressure, resulting in good joint performance, but it involves high welding temperature, long welding time, and high cost. Furthermore, for combinations of materials with large differences in thermal expansion coefficients, residual stress is still difficult to avoid. Anodic welding utilizes an electric field to achieve a connection, resulting in low welding temperature and low residual stress, but it is only suitable for glasses containing alkali metal ions, limiting its application range.

[0005] Laser welding is the fastest-growing welding method in recent years, boasting advantages such as high welding speed, small heat-affected zone, and high precision, and is considered the most promising method for joining glass and metal. However, existing laser welding technology still faces many unresolved problems: First, the interfacial bonding strength is low, and the wettability of liquid metal on the glass surface is poor, making it difficult to form a good metallurgical bond. Secondly, the residual stress is large. The thermal expansion coefficients of glass and metal are very different, which will generate a lot of residual stress during the welding process, causing the joint to crack during cooling or use. Third, glass is prone to cracking. The high energy density of lasers can easily cause local overheating of the glass, resulting in thermal stress cracks. Fourth, it has poor high-temperature performance. Existing stress relief structures will fail at high temperatures, resulting in a sharp decline in joint strength and airtightness. Fifth, it has low long-term reliability, and oxidation and diffusion easily occur at the interface, causing the joint performance to gradually degrade over time.

[0006] To address these issues, researchers have conducted extensive studies. For example, some have proposed fabricating an intermediate layer on the glass surface to improve wettability and relieve stress. However, most existing intermediate layers are prepared using the sol-gel method, which suffers from poor thickness uniformity, weak adhesion to the substrate, and low density, making it difficult to meet high airtightness requirements. Others have proposed fabricating microgroove structures on metal surfaces and filling them with low-melting-point alloys to release stress. However, this structure softens and fails at high temperatures, and laser etching of microgrooves can create microcracks and heat-affected zones on the metal surface, reducing the strength of the base metal. Additionally, some have proposed using ultrasonic-assisted laser welding to improve wettability. However, traditional ultrasonic vibration is applied to the workpiece via an amplitude transformer, resulting in low energy transfer efficiency and a tendency to cause microcracks in brittle glass.

[0007] Therefore, there is an urgent need to develop a new high-airtightness welding method for glass and metal dissimilar materials that can effectively solve all the above-mentioned technical problems, so as to meet the demand of modern high-end manufacturing fields for high-performance welded joints used in extreme environments. Summary of the Invention

[0008] To address the problems in the prior art, this invention provides a high-airtightness welding method for dissimilar materials such as glass and metal, which solves the problems of weak interfacial bonding, incomplete stress release, easy cracking of glass, poor high-temperature performance, and low long-term reliability in the prior art.

[0009] The technical solution adopted by this invention to solve its technical problem is: a method for high airtightness welding of dissimilar materials such as glass and metal, comprising the following steps: S1 Surface Collaborative Pretreatment: Place the glass and metal workpieces to be welded into a low-temperature plasma treatment chamber, and introduce a mixture of argon and hydrogen gas with a volume ratio of (3-5):1. Treat for 5-15 minutes under the conditions of 100-300W power and 10-50Pa pressure to remove surface contaminants and form an activated surface. S2 Atomic-Level Composition Gradient Interface Layer Preparation: Plasma-enhanced atomic layer deposition technology is used to prepare a composition gradient interface layer with a thickness of 20-100 nm on the pretreated glass surface to be welded. The interface layer consists of a silicon-rich layer, a continuous transition layer and a metal-rich layer from the glass side to the metal side, with no obvious interface between the layers. S3 Dual Stress Self-Release Structure Preparation: A periodic microgroove array is prepared on the pretreated metal surface to be welded using femtosecond laser etching technology. Then, the metal surface is subjected to nanocrystallization treatment to form a nanocrystalline layer with a thickness of 5-20μm on the sidewalls and bottom of the microgroove. Finally, the microgroove is filled with a tin-bismuth low-melting-point alloy with rare earth elements. S4 laser-induced ultrasonic-assisted dual-pulse laser welding: The prepared glass and metal workpieces are assembled and fixed so that the surfaces to be welded are in close contact. A pulsed laser is used to excite ultrasonic vibration in the non-welding area of ​​the metal surface, while a femtosecond-nanosecond dual-pulse laser is used to scan and weld along the welding trajectory. S5 Composite Post-treatment: After welding, first cool to 200℃ at a rate of 5-10℃ / min, then cool to room temperature at a rate of 1-3℃ / min, and then perform electric field-assisted low-temperature annealing treatment for 1-3 hours at 150-250℃ and an electric field strength of 500-2000V / m.

[0010] Specifically, the plasma-enhanced atomic layer deposition in step S2 has a deposition temperature of 100-200℃ and a thickness of 0.1-0.2nm per deposition cycle. The composition gradient is achieved by continuously changing the ratio of silicon source to metal source.

[0011] Specifically, in step S2, the silicon atom content of the silicon-rich layer is greater than 90%, the metal atom content of the metal-rich layer is greater than 85%, and the composition of the continuous transition layer changes linearly from the silicon-rich layer to the metal-rich layer.

[0012] Specifically, in step S3, the pulse width of the femtosecond laser etching is 100-500 fs, the repetition frequency is 100-1000 kHz, the microgroove depth is 1 / 12-1 / 6 of the metal plate thickness, the width is 1-1.5 times the depth, and the spacing is 4-6 times the width.

[0013] Specifically, the nanocrystallization treatment in step S3 employs laser shock peening technology with a laser power density of 10. 9 -10 10 W / cm 2 The number of impacts is 1-3, and the average grain size of the formed nanocrystalline layer is 20-100nm.

[0014] Specifically, the modified low-melting-point alloy described in step S3 is composed of tin, bismuth, silver with a mass fraction of 0.5-2%, and lanthanum with a mass fraction of 0.1-0.5%, with a melting point of 100-180℃.

[0015] Specifically, in step S4, the excitation laser wavelength of the laser-induced ultrasound is 1064nm, the pulse width is 10-50ns, the repetition frequency is the same as that of the welding laser, and the distance between the excitation point and the welding trajectory is 1-3mm.

[0016] Specifically, in step S4, the timing of the femtosecond-nanosecond dual-pulse laser is such that the femtosecond laser leads the nanosecond laser by 50-200 ns, and the power density of the femtosecond laser is 10. 11 -10 12 W / cm 2 The nanosecond laser power density is 10 8 -10 9 W / cm 2 .

[0017] Specifically, the glass is quartz glass, borosilicate glass, or aluminosilicate glass, and the metal is stainless steel, titanium alloy, or Kovar alloy.

[0018] The glass-metal welded joint prepared by the above-mentioned high-airtightness welding method for dissimilar glass and metal materials still exhibits a helium leakage rate of less than 1×10⁻⁶ after being held at 150°C for 1000 hours. -12 Pa·m 3 / s, shear strength retention rate is greater than 85%.

[0019] The beneficial effects of this invention are: This invention uses plasma-enhanced atomic layer deposition (PEAD) technology to prepare an atomic-level compositional gradient interface layer, achieving a continuous linear change in the coefficient of thermal expansion. The interface layer has extremely high density, uniformity, and bonding strength, which can effectively alleviate residual stress and significantly improve the airtightness of the joint.

[0020] This invention prepares a dual stress-releasing structure combining a femtosecond laser microgroove array and surface nanocrystallization. Combined with the filling of modified low-melting-point alloy, it achieves stress release across the entire temperature range from room temperature to high temperature, significantly improving the joint's strength and high-temperature performance.

[0021] This invention employs laser-induced ultrasonic-assisted femtosecond-nanosecond dual-pulse laser welding technology, which avoids damage to glass caused by traditional ultrasonic vibration. At the same time, it utilizes the non-equilibrium melting characteristics of femtosecond lasers and the metallurgical bonding characteristics of nanosecond lasers to achieve high-quality welding and effectively prevent glass cracking.

[0022] This invention employs a combined post-treatment technique of gradient cooling and electric field-assisted low-temperature annealing, which can completely eliminate residual stress, repair interface defects, and significantly improve the long-term reliability of the joint.

[0023] The welding method of the present invention has good process controllability, is easy to automate, and produces welded joints with excellent comprehensive performance, which can meet the usage requirements of aerospace, nuclear industry, deep-sea equipment and other extreme environments. Attached Figure Description

[0024] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0025] Figure 1 The flowchart shows the high airtightness welding method for dissimilar glass and metal materials provided by the present invention. Detailed Implementation

[0026] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0027] like Figure 1 As shown, the high airtightness welding method for dissimilar glass and metal materials according to the present invention includes the following steps: S1 Surface Synergistic Pretreatment: Glass and metal workpieces to be welded are ultrasonically cleaned for 10-15 minutes with anhydrous ethanol and deionized water, respectively, to remove surface oil and dust. They are then placed in a low-temperature plasma treatment chamber. A mixture of argon and hydrogen gas with a volume ratio of (3-5):1 is introduced, and treatment is performed for 5-15 minutes at a power of 100-300W and a pressure of 10-50Pa. Argon plasma removes the oxide film and stubborn contaminants from the surface through physical sputtering, while simultaneously increasing surface roughness. Hydrogen plasma reduces the oxide film on the metal surface through chemical reduction and removes adsorbed water and hydroxyl groups from the glass surface. After synergistic pretreatment, the surface energy of both the glass and metal surfaces is significantly improved, providing a good foundation for subsequent interface layer preparation and welding processes.

[0028] S2 Atomic-Level Composition Gradient Interface Layer Preparation: Plasma-Enhanced Atomic Layer Deposition (PEALD) technology was used to prepare a composition gradient interface layer with a thickness of 20-100 nm on the pretreated glass surface to be welded. PEALD technology is a thin film deposition technique based on self-limiting reaction, which can precisely control the thickness and composition of the film at the atomic level. The prepared film has extremely high density, uniformity and adhesion to the substrate.

[0029] The preparation process of the composition gradient interface layer is as follows: First, using trimethylaluminum and water as precursors, a silicon-rich layer (actually a silicon dioxide layer) with a thickness of 5-20 nm is deposited, with a silicon atom content greater than 90%, exhibiting excellent compatibility with the glass substrate. Then, the ratio of silicon source (tetraethyl orthosilicate) to metal source (such as trimethylaluminum, titanium tetrachloride, etc.) is continuously changed, causing the composition of the deposited film to gradually transition from silicon-rich to metal-rich, forming a continuous transition layer with a thickness of 10-60 nm. Finally, using a metal source as the sole precursor, a metal-rich layer with a thickness of 5-20 nm is deposited, with a metal atom content greater than 85%, exhibiting excellent compatibility with the metal substrate. The temperature throughout the deposition process is controlled at 100-200℃ to prevent glass deformation.

[0030] The atomically graded interface layer exhibits a continuous linear change in the coefficient of thermal expansion from the glass side to the metal side, effectively mitigating residual stress caused by the difference in thermal expansion coefficients between the glass and metal. Simultaneously, the atomically dense interface layer effectively blocks the penetration of gas molecules, significantly improving the gas tightness of the joint. Furthermore, the interface layer is chemically bonded to both the glass and metal, exhibiting extremely high bonding strength and preventing detachment during welding or use.

[0031] Fabrication of the S3 dual-stress self-releasing structure: A periodic microgroove array was fabricated on the pretreated metal surface to be welded using femtosecond laser etching technology. The femtosecond laser has an extremely short pulse width, resulting in a near-zero heat-affected zone and preventing microcracks and thermal damage on the metal surface. The depth of the microgrooves is 1 / 12 to 1 / 6 of the metal plate thickness, the width is 1 to 1.5 times the depth, the spacing is 4 to 6 times the width, the cross-sectional shape is trapezoidal, the upper base width is greater than the lower base width, and the sidewall inclination angle is 65-85 degrees.

[0032] After the microgroove array was fabricated, the metal surface was nanocrystallized using laser shock irradiation (LSI). SSI utilizes a high-power-density laser to irradiate the metal surface, causing explosive vaporization of the surface material and generating a high-pressure shock wave, thereby refining the metal surface grains to the nanoscale. After treatment, a nanocrystalline layer with a thickness of 5-20 μm is formed on the metal surface, including the sidewalls and bottom of the microgrooves, with an average grain size of 20-100 nm. Nanocrystalline metals possess extremely high plastic deformation capabilities, absorbing a large amount of residual stress through plastic deformation.

[0033] Finally, a modified tin-bismuth low-melting-point alloy with added rare-earth element lanthanum was filled into the microgroove. This alloy, with a melting point of 100-180℃, consists of tin, bismuth, 0.5-2% silver by mass, and 0.1-0.5% lanthanum by mass. The addition of lanthanum significantly improves the alloy's oxidation resistance and high-temperature strength, while also enhancing its wettability with the base metal.

[0034] The working principle of the dual-stress self-releasing structure is as follows: During welding, when the temperature rises above the melting point of the low-melting-point alloy, the alloy within the microgroove melts, turning the microgroove into a cavity. At this point, the highly ductile nanocrystalline metal can undergo plastic deformation into the microgroove, absorbing some of the thermal expansion and reducing the thermal expansion difference between the glass and the metal. Upon cooling after welding, the low-melting-point alloy resolidifies, filling the microgroove and restoring the integrity of the metal workpiece. Simultaneously, during cooling, when the residual stress exceeds the yield strength of the nanocrystalline metal, the nanocrystalline layer undergoes uniform plastic deformation, further releasing the residual stress. Furthermore, even when the low-melting-point alloy softens at high temperatures, the nanocrystalline layer still maintains excellent stress release capabilities, thus significantly improving the high-temperature performance of the joint.

[0035] S4 Laser-Induced Ultrasonic Assisted Dual-Pulse Laser Welding: The prepared glass and metal workpieces are assembled and fixed, ensuring a tight fit between the surfaces to be welded, with a gap of less than 5μm. A pulsed laser is used to excite ultrasonic vibrations in the non-welding area of ​​the metal surface, with the excitation point 1-3mm from the welding trajectory. Laser-induced ultrasound utilizes pulsed laser irradiation of the metal surface, causing the surface material to expand instantaneously due to heat, thereby exciting high-frequency ultrasonic waves. This ultrasonic wave is generated directly on the metal surface, resulting in extremely high energy transfer efficiency and causing no damage to the glass workpiece.

[0036] Simultaneously, a femtosecond-nanosecond dual-pulse laser is used for scanning welding along the welding trajectory. The timing of the dual-pulse laser is such that the femtosecond laser leads the nanosecond laser by 50-200 ns. The power density of the femtosecond laser is 10. 11 -10 12 W / cm 2 With a pulse width of 100-500 fs, nanosecond lasers can generate extremely rapid heating and cooling at the interface, causing non-equilibrium melting of glass and metal surfaces to form nanocrystalline structures, while preventing the glass from overheating and cracking. The power density of nanosecond lasers is 10-1. 8 -10 9 W / cm 2 With a pulse width of 10-100ns, it can provide enough energy to fully mix the materials at the interface and form a good metallurgical bond.

[0037] Laser-induced ultrasound plays the following roles in the welding process: First, it generates a cavitation effect, which can break up brittle metal oxides generated at the interface and avoid the influence of brittleness on the joint performance; second, it generates an acoustic flow effect, which can promote the wetting and spreading of liquid metal on the glass surface and improve the interfacial bonding strength; third, it generates a vibration stirring effect, which can refine the grains at the interface and improve the microstructure of the joint; and fourth, it can accelerate atomic diffusion and promote chemical bonding at the interface.

[0038] S5 Composite Post-Treatment: After welding, cool to 200℃ at a rate of 5-10℃ / min, then cool to room temperature at a rate of 1-3℃ / min. Gradient cooling avoids thermal shock caused by excessively rapid cooling, further reducing residual stress. Then, place the welded joint in an electric field annealing furnace and perform field-assisted low-temperature annealing for 1-3 hours at 150-250℃ and an electric field strength of 500-2000V / m. Field-assisted annealing promotes atomic diffusion, accelerates the release of residual stress, repairs interface defects, improves chemical bonding at the interface, and significantly improves the long-term reliability of the joint.

[0039] Example 1: This example provides a high-airtightness welding method for quartz glass and 304 stainless steel. The specific steps are as follows: S1. Surface Co-treatment: A 2mm thick quartz glass sheet and a 1mm thick 304 stainless steel sheet were ultrasonically cleaned for 12 minutes each with anhydrous ethanol and deionized water, respectively, and then placed in a low-temperature plasma treatment chamber. A mixture of argon and hydrogen gas with a volume ratio of 4:1 was introduced, and the treatment was carried out for 10 minutes at a power of 200W and a pressure of 30Pa. After treatment, the workpieces were removed and immediately proceeded to the next step to avoid secondary contamination of the surface.

[0040] S2. Preparation of Atomic-Level Composition Gradient Interface Layer: A composition gradient interface layer was prepared on the quartz glass surface to be soldered using plasma-enhanced atomic layer deposition (PEALD). The deposition temperature was 150℃, and the working pressure was 10 Pa. First, using tetraethyl orthosilicate and water as precursors, 100 deposition cycles were performed to form a 10 nm thick silicon-rich layer with a silicon atom content of 92%. Then, in the next 300 deposition cycles, the proportion of trimethylaluminum was continuously increased while the proportion of tetraethyl orthosilicate was decreased to form a 30 nm thick continuous transition layer, with the composition gradually transitioning from silicon dioxide to alumina. Finally, using trimethylaluminum and water as precursors, 100 deposition cycles were performed to form a 10 nm thick metal-rich layer with an aluminum atom content of 88%. The total thickness of the prepared composition gradient interface layer was 50 nm, with no obvious interfaces between the layers.

[0041] S3. Fabrication of a Dual Stress Self-Release Structure: A periodic microgroove array was fabricated on the surface of a 304 stainless steel sheet to be welded using femtosecond laser etching technology. The femtosecond laser had a wavelength of 1030 nm, a pulse width of 300 fs, a repetition frequency of 500 kHz, and a power of 10 W. The microgroove depth was 0.12 mm, the upper base width was 0.15 mm, the lower base width was 0.12 mm, the sidewall tilt angle was 75 degrees, and the spacing was 0.6 mm. After the microgroove array was fabricated, the stainless steel surface was nanocrystallized using laser shock peening technology. The laser power density was 5 × 10⁻⁶. 9 W / cm 2The pulse width was 10 ns, the repetition frequency was 1 Hz, and the number of impacts was 2. After treatment, a nanocrystalline layer with a thickness of 10 μm and an average grain size of 50 nm was formed on the stainless steel surface. Finally, a modified tin-bismuth-silver-lanthanum alloy (62% tin, 36.5% bismuth, 1% silver, 0.5% lanthanum, melting point 135℃) was heated to 170℃ to melt it. The molten alloy was filled into the microgroove using micro-injection technology. After cooling to room temperature, the surface was polished smooth with diamond sandpaper, and the surface roughness was less than 0.8 μm.

[0042] S4. Laser-Induced Ultrasonic-Assisted Dual-Pulse Laser Welding: The prepared quartz glass sheet and 304 stainless steel sheet are assembled and fixed, ensuring a tight fit between the surfaces to be welded, with an assembly gap of less than 3 μm. A pulsed laser with a wavelength of 1064 nm, a pulse width of 20 ns, and a repetition frequency of 10 kHz is used to excite ultrasonic vibration on the stainless steel surface. The distance between the excitation point and the welding trajectory is 2 mm. Simultaneously, a femtosecond-nanosecond dual-pulse laser is used for welding, with the femtosecond laser leading the nanosecond laser by 100 ns. The femtosecond laser has a wavelength of 1030 nm, a pulse width of 300 fs, and a power density of 5 × 10⁻⁶. 11 W / cm 2 The nanosecond laser has a wavelength of 1064 nm, a pulse width of 50 ns, and a power density of 5 × 10⁻⁶. 8 W / cm 2 The welding scanning speed was 10 mm / s, and the defocusing amount was 0 mm. The entire welding process was carried out under an argon protective atmosphere with an argon flow rate of 10 L / min.

[0043] S5. Post-treatment: After welding, cool to 200℃ at a rate of 8℃ / min, then cool to room temperature at a rate of 2℃ / min. Then, place the welded joint in an electric field annealing furnace and perform electric field-assisted low-temperature annealing treatment for 2 hours at 200℃ and an electric field strength of 1000V / m.

[0044] Performance testing: A comprehensive performance test was conducted on the quartz glass-304 stainless steel welded joint prepared in this embodiment, and the results are as follows: Helium leakage rate: Vacuum leak detection was performed using a helium mass spectrometer, and the leakage rate was 3.2 × 10⁻⁶. -13 Pa·m 3 / s; Room temperature shear strength: Tested using a universal testing machine, the average shear strength was 148 MPa, reaching 92% of the strength of the quartz glass matrix. High-temperature shear strength: Tested at 150℃, the average shear strength was 128 MPa, and the strength retention rate was 86.5%. Thermal cycling life: After 1500 cycles of thermal cycling testing between -50℃ and 150℃, the joint showed no cracks or leaks, and the leakage rate remained at 3.8×10⁻⁶. -13 Pa·m 3 / s; Long-term stability: After being kept at 150℃ for 1000 hours, the shear strength of the joint was 125MPa, the strength retention rate was 84.5%, and the leakage rate did not change significantly.

[0045] Referring to Example 1, the most advanced ultrasonic-assisted laser welding method currently available is used to weld quartz glass and 304 stainless steel. The specific steps are as follows: Quartz glass and 304 stainless steel sheets were ultrasonically cleaned for 12 minutes each with anhydrous ethanol and deionized water, respectively. A 100 nm thick silica-alumina gradient intermediate layer was prepared on the glass surface using a sol-gel method. A microgroove array was fabricated on the stainless steel surface using a nanosecond laser and filled with a tin-bismuth-silver alloy. The workpieces were assembled and fixed, and ultrasonic vibration at a frequency of 30 kHz and an amplitude of 10 μm was applied. Welding was then performed using a nanosecond pulsed laser. After welding, the surfaces were allowed to cool naturally to room temperature and then subjected to conventional annealing at 200 °C for 2 hours.

[0046] Performance testing: The performance of the welded joint prepared in Comparative Example 1 was tested, and the results are as follows: Helium leakage rate: 2.6 × 10 -11 Pa·m 3 / s; Room temperature shear strength: The average shear strength is 95 MPa; High-temperature shear strength: Tested at 150℃, the average shear strength was 52MPa, and the strength retention rate was 54.7%. Thermal cycling life: After 320 cycles of thermal cycling test between -50℃ and 150℃, microcracks appeared in the joint and the leakage rate increased sharply. Long-term stability: After being kept at 150℃ for 1000 hours, the joint's shear strength was 45 MPa, with a strength retention rate of 47.4%, and the leakage rate exceeded 1×10⁻⁶. -8 Pa·m 3 / s.

[0047] Example 2: This example provides a high-airtightness welding method for borosilicate glass and TC4 titanium alloy. The specific steps are as follows: S1. Surface Co-treatment: A 3mm thick borosilicate glass sheet and a 1.5mm thick TC4 titanium alloy sheet were ultrasonically cleaned for 15 minutes each with anhydrous ethanol and deionized water, respectively, and then placed in a low-temperature plasma treatment chamber. A mixture of argon and hydrogen gas with a volume ratio of 5:1 was introduced, and the treatment was carried out for 12 minutes at a power of 250W and a pressure of 40Pa. After treatment, the workpieces were removed and immediately proceeded to the next step.

[0048] S2. Preparation of Atomic-Level Composition Gradient Interface Layer: A composition gradient interface layer was prepared on the borosilicate glass surface to be soldered using plasma-enhanced atomic layer deposition (PEALD). The deposition temperature was 180℃, and the working pressure was 15 Pa. First, using tetraethyl orthosilicate and water as precursors, 80 deposition cycles were performed to form a silicon-rich layer with a thickness of 8 nm and a silicon atom content of 91%. Then, in the next 250 deposition cycles, the proportion of titanium tetrachloride was continuously increased while the proportion of tetraethyl orthosilicate was decreased to form a continuous transition layer with a thickness of 25 nm, where the composition gradually transitioned from silicon dioxide to titanium dioxide. Finally, using titanium tetrachloride and water as precursors, 80 deposition cycles were performed to form a metal-rich layer with a thickness of 8 nm and a titanium atom content of 87%. The total thickness of the prepared composition gradient interface layer was 41 nm.

[0049] S3. Fabrication of a Dual Stress Self-Release Structure: A periodic microgroove array was fabricated on the surface of a TC4 titanium alloy sheet to be welded using femtosecond laser etching technology. The femtosecond laser had a wavelength of 1030 nm, a pulse width of 200 fs, a repetition rate of 800 kHz, and a power of 12 W. The microgroove depth was 0.18 mm, the upper base width was 0.22 mm, the lower base width was 0.18 mm, the sidewall tilt angle was 70 degrees, and the spacing was 0.8 mm. After the microgroove array was fabricated, the titanium alloy surface was nanocrystallized using laser shock peening technology. The laser power density was 8 × 10⁻⁶. 9 W / cm 2 The pulse width was 8 ns, the repetition frequency was 1 Hz, and the number of impacts was 3. After treatment, a nanocrystalline layer with a thickness of 15 μm and an average grain size of 30 nm was formed on the surface of the titanium alloy. Finally, a modified tin-bismuth-silver-lanthanum alloy (59% tin, 39.2% bismuth, 1.5% silver, 0.3% lanthanum, melting point 125℃) was heated to 160℃ to melt it. The molten alloy was then filled into microgrooves using micro-injection technology. After cooling to room temperature, the surface was polished smooth with diamond sandpaper.

[0050] S4. Laser-Induced Ultrasonic-Assisted Dual-Pulse Laser Welding: The prepared borosilicate glass sheet and TC4 titanium alloy sheet are assembled and fixed to ensure tight contact between the surfaces to be welded, with an assembly gap of less than 4 μm. A pulsed laser with a wavelength of 1064 nm, a pulse width of 15 ns, and a repetition frequency of 8 kHz is used to excite ultrasonic vibration on the titanium alloy surface. The distance between the excitation point and the welding trajectory is 2.5 mm. Simultaneously, a femtosecond-nanosecond dual-pulse laser is used for welding, with the femtosecond laser leading the nanosecond laser by 150 ns. The femtosecond laser has a wavelength of 1030 nm, a pulse width of 200 fs, and a power density of 8 × 10⁻⁶. 11 W / cm 2 The nanosecond laser has a wavelength of 1064 nm, a pulse width of 40 ns, and a power density of 6 × 10⁻⁶. 8 W / cm 2 The welding scanning speed was 8 mm / s, and the defocusing amount was -0.3 mm. The entire welding process was carried out under an argon protective atmosphere with an argon flow rate of 12 L / min.

[0051] S5. Post-treatment: After welding, cool to 200℃ at a rate of 7℃ / min, then cool to room temperature at a rate of 1.5℃ / min. Then, place the welded joint in an electric field annealing furnace and perform electric field-assisted low-temperature annealing treatment for 1.5 hours at 220℃ and an electric field strength of 1500V / m.

[0052] Performance testing: The performance of the borosilicate glass-TC4 titanium alloy welded joint prepared in this embodiment was tested, and the results are as follows: Helium leakage rate: 4.1 × 10 -13 Pa·m 3 / s; Room temperature shear strength: The average shear strength is 136 MPa, reaching 90% of the strength of the borosilicate glass matrix; High-temperature shear strength: Tested at 150℃, the average shear strength was 118 MPa, and the strength retention rate was 86.8%. Thermal cycling life: After 1500 cycles of thermal cycling test between -60℃ and 160℃, the joint showed no cracks or leaks. Long-term stability: After being kept at 150℃ for 1000 hours, the shear strength of the joint was 116MPa, the strength retention rate was 85.3%, and the leakage rate did not change significantly.

[0053] Referring to Example 2, the diffusion soldering method with added copper interlayer is used to weld borosilicate glass and TC4 titanium alloy. The specific steps are as follows: Borosilicate glass sheets and TC4 titanium alloy sheets were ultrasonically cleaned for 15 minutes each with anhydrous ethanol and deionized water, respectively. A 0.1 mm thick copper foil was placed between the glass and titanium alloy as an interlayer, and then the sheets were placed in a diffusion bonding furnace. The furnace was operated under a vacuum of 1×10⁻⁶. -3 The furnace was kept at 850°C and 10MPa for 2 hours, and then cooled to room temperature with the furnace.

[0054] Performance testing: The performance of the welded joint prepared in Comparative Example 2 was tested, and the results are as follows: Helium leakage rate: 1.8 × 10 -10 Pa·m 3 / s; Room temperature shear strength: The average shear strength is 72 MPa; High-temperature shear strength: Tested at 150℃, the average shear strength was 48MPa, and the strength retention rate was 66.7%. Thermal cycling life: After 180 cycles of thermal cycling test between -60℃ and 160℃, obvious cracks appeared in the joint; Long-term stability: After being kept at 150℃ for 1000 hours, the joint's shear strength was 35 MPa, with a strength retention rate of 48.6%, and the leakage rate exceeded 1×10⁻⁶. -7 Pa·m 3 / s.

[0055] Example 3: This example provides a high-airtightness welding method for aluminosilicate glass and 4J29 Kovar alloy. The specific steps are as follows: S1. Surface Co-treatment: A 2.5mm thick aluminosilicate glass sheet and a 1.2mm thick 4J29 Kovar alloy sheet were ultrasonically cleaned for 10 minutes each with anhydrous ethanol and deionized water, respectively, and then placed in a low-temperature plasma treatment chamber. A mixture of argon and hydrogen gas with a volume ratio of 3.5:1 was introduced, and the treatment was carried out for 8 minutes at a power of 180W and a pressure of 25Pa. After treatment, the workpiece was removed and immediately proceeded to the next step.

[0056] S2. Preparation of Atomic-Level Composition Gradient Interface Layer: A composition gradient interface layer was prepared on the aluminosilicate glass surface to be soldered using plasma-enhanced atomic layer deposition (PEALD). The deposition temperature was 120℃, and the working pressure was 8 Pa. First, using tetraethyl orthosilicate and water as precursors, 120 deposition cycles were performed to form a silicon-rich layer with a thickness of 12 nm and a silicon atom content of 93%. Then, in the next 350 deposition cycles, the proportion of ferrocene was continuously increased while the proportion of tetraethyl orthosilicate was decreased to form a continuous transition layer with a thickness of 35 nm, where the composition gradually transitioned from silicon dioxide to iron oxide. Finally, using ferrocene and oxygen as precursors, 120 deposition cycles were performed to form a metal-rich layer with a thickness of 12 nm and an iron atom content of 89%. The total thickness of the prepared composition gradient interface layer was 59 nm.

[0057] S3. Fabrication of a Dual Stress Self-Release Structure: A periodic microgroove array was fabricated on the surface of a 4J29 Kovar alloy sheet to be welded using femtosecond laser etching technology. The femtosecond laser had a wavelength of 1030 nm, a pulse width of 400 fs, a repetition rate of 300 kHz, and a power of 8 W. The microgroove depth was 0.15 mm, the upper base width was 0.18 mm, the lower base width was 0.15 mm, the sidewall tilt angle was 80 degrees, and the spacing was 0.7 mm. After the microgroove array was fabricated, the Kovar alloy surface was nanocrystallized using laser shock peening technology. The laser power density was 3 × 10⁻⁶. 9 W / cm 2 The pulse width was 12 ns, the repetition frequency was 1 Hz, and the number of impacts was 1. After treatment, a nanocrystalline layer with a thickness of 8 μm and an average grain size of 70 nm was formed on the Kovar alloy surface. Finally, a modified tin-bismuth-silver-lanthanum alloy (64% tin, 34.7% bismuth, 1% silver, 0.3% lanthanum, melting point 140℃) was heated to 180℃ to melt it. The molten alloy was then filled into microgrooves using micro-injection technology. After cooling to room temperature, the surface was polished smooth with diamond sandpaper.

[0058] S4. Laser-Induced Ultrasonic-Assisted Dual-Pulse Laser Welding: The prepared aluminosilicate glass sheet and 4J29 Kovar alloy sheet are assembled and fixed to ensure tight contact between the surfaces to be welded, with an assembly gap of less than 2μm. A pulsed laser with a wavelength of 1064nm, a pulse width of 30ns, and a repetition frequency of 12kHz is used to excite ultrasonic vibrations on the Kovar alloy surface. The distance between the excitation point and the welding trajectory is 1.5mm. Simultaneously, a femtosecond-nanosecond dual-pulse laser is used for welding, with the femtosecond laser leading the nanosecond laser by 80ns. The femtosecond laser has a wavelength of 1030nm, a pulse width of 400fs, and a power density of 3×10⁻⁶. 11 W / cm 2 The nanosecond laser has a wavelength of 1064 nm, a pulse width of 60 ns, and a power density of 4 × 10⁻⁶. 8 W / cm2 The welding scanning speed was 12 mm / s, and the defocusing amount was +0.2 mm. The entire welding process was carried out under an argon protective atmosphere with an argon flow rate of 8 L / min.

[0059] S5. Post-treatment: After welding, cool to 200℃ at a rate of 6℃ / min, then cool to room temperature at a rate of 1℃ / min. Then, place the welded joint in an electric field annealing furnace and perform electric field-assisted low-temperature annealing treatment for 2.5 hours at 180℃ and an electric field strength of 800V / m.

[0060] Performance testing: The performance of the aluminosilicate glass-4J29 Kovar alloy welded joint prepared in this embodiment was tested, and the results are as follows: Helium leakage rate: 2.8 × 10 -13 Pa·m 3 / s; Room temperature shear strength: The average shear strength is 152 MPa, reaching 93% of the strength of the aluminosilicate glass matrix; High-temperature shear strength: Tested at 150℃, the average shear strength was 132 MPa, and the strength retention rate was 86.8%. Thermal cycling life: After 1500 cycles of thermal cycling test between -40℃ and 140℃, the joint showed no cracks or leaks. Long-term stability: After being kept at 150℃ for 1000 hours, the shear strength of the joint was 130MPa, the strength retention rate was 85.5%, and the leakage rate did not change significantly.

[0061] Referring to Example 3, the traditional flame brazing method is used to weld aluminosilicate glass and 4J29 Kovar alloy. The specific steps are as follows: The aluminosilicate glass slide and the 4J29 Kovar alloy sheet were ultrasonically cleaned for 10 minutes each with anhydrous ethanol and deionized water, respectively. A silver-copper-titanium solder foil was placed between the glass and the Kovar alloy, and flux was applied. Heating was performed using an oxyacetylene flame until the solder melted at 800°C. Heating was maintained at this temperature for 1 minute, then the solution was removed and allowed to cool naturally to room temperature. Finally, the solution was cleaned with acetone to remove any residual flux.

[0062] Performance testing: The performance of the welded joint prepared in Comparative Example 3 was tested, and the results are as follows: Helium leakage rate: 5.3 × 10 -9 Pa·m 3 / s; Room temperature shear strength: The average shear strength is 68 MPa; High-temperature shear strength: Tested at 150℃, the average shear strength was 32MPa, and the strength retention rate was 47.1%. Thermal cycling life: After 90 cycles of thermal cycling test between -40℃ and 140℃, cracks appeared in the joint; Long-term stability: After being kept at 150℃ for 1000 hours, the shear strength of the joint is 25MPa, the strength retention rate is 36.8%, and the leakage rate exceeds 1×10⁻⁶. -6 Pa·m 3 / s.

[0063] The performance test results of the above embodiments and comparative examples clearly show that the glass-metal dissimilar material high airtightness welding method of the present invention is significantly superior to the prior art in terms of airtightness, room temperature strength, high temperature strength, thermal cycle life and long-term stability, and can meet the requirements for use in extreme environments.

[0064] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of protection claimed by the present invention. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for high-airtightness welding of dissimilar materials, glass and metal, characterized in that, Includes the following steps: S1 Surface Collaborative Pretreatment: Place the glass and metal workpieces to be welded into a low-temperature plasma treatment chamber, and introduce a mixture of argon and hydrogen gas with a volume ratio of (3-5):

1. Treat for 5-15 minutes under the conditions of 100-300W power and 10-50Pa pressure to remove surface contaminants and form an activated surface. S2 Atomic-Level Composition Gradient Interface Layer Preparation: Plasma-enhanced atomic layer deposition technology is used to prepare a composition gradient interface layer with a thickness of 20-100 nm on the pretreated glass surface to be welded. The interface layer consists of a silicon-rich layer, a continuous transition layer and a metal-rich layer from the glass side to the metal side, with no obvious interface between the layers. S3 Dual Stress Self-Release Structure Preparation: A periodic microgroove array is prepared on the pretreated metal surface to be welded using femtosecond laser etching technology. Then, the metal surface is subjected to nanocrystallization treatment to form a nanocrystalline layer with a thickness of 5-20μm on the sidewalls and bottom of the microgroove. Finally, the microgroove is filled with a tin-bismuth low-melting-point alloy with rare earth elements. S4 laser-induced ultrasonic-assisted dual-pulse laser welding: The prepared glass and metal workpieces are assembled and fixed so that the surfaces to be welded are in close contact. A pulsed laser is used to excite ultrasonic vibration in the non-welding area of ​​the metal surface, while a femtosecond-nanosecond dual-pulse laser is used to scan and weld along the welding trajectory. S5 Composite Post-treatment: After welding, first cool to 200℃ at a rate of 5-10℃ / min, then cool to room temperature at a rate of 1-3℃ / min, and then perform electric field-assisted low-temperature annealing treatment for 1-3 hours at 150-250℃ and an electric field strength of 500-2000V / m.

2. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: The plasma-enhanced atomic layer deposition in step S2 has a deposition temperature of 100-200℃ and a thickness of 0.1-0.2nm per deposition cycle. The composition gradient is achieved by continuously changing the ratio of silicon source to metal source.

3. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: In step S2, the silicon atom content of the silicon-rich layer is greater than 90%, the metal atom content of the metal-rich layer is greater than 85%, and the composition of the continuous transition layer changes linearly from the silicon-rich layer to the metal-rich layer.

4. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: In step S3, the pulse width of the femtosecond laser etching is 100-500 fs, the repetition frequency is 100-1000 kHz, the microgroove depth is 1 / 12-1 / 6 of the metal plate thickness, the width is 1-1.5 times the depth, and the spacing is 4-6 times the width.

5. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: The nanocrystallization treatment in step S3 employs laser shock peening technology with a laser power density of 10. 9 -10 10 W / cm 2 The number of impacts is 1-3, and the average grain size of the formed nanocrystalline layer is 20-100nm.

6. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: The modified low-melting-point alloy described in step S3 is composed of tin, bismuth, silver with a mass fraction of 0.5-2%, and lanthanum with a mass fraction of 0.1-0.5%, with a melting point of 100-180℃.

7. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: In step S4, the excitation laser wavelength of the laser-induced ultrasound is 1064nm, the pulse width is 10-50ns, the repetition frequency is the same as that of the welding laser, and the distance between the excitation point and the welding trajectory is 1-3mm.

8. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: The timing sequence of the femtosecond-nanosecond dual-pulse laser in step S4 is that the femtosecond laser leads the nanosecond laser by 50-200 ns, and the power density of the femtosecond laser is 10. 11 -10 12 W / cm 2 The nanosecond laser power density is 10 8 -10 9 W / cm 2 .

9. The method for high airtightness welding of dissimilar glass and metal materials according to claim 1, characterized in that: The glass is quartz glass, borosilicate glass, or aluminosilicate glass, and the metal is stainless steel, titanium alloy, or Kovar alloy.

10. The glass-metal welded joint prepared by the high airtightness welding method for dissimilar glass and metal materials according to claim 1, characterized in that, The helium leakage rate of the welded joint after being held at 150°C for 1000 hours was still less than 1×10⁻⁶. -12 Pa·m 3 / s, shear strength retention rate is greater than 85%.